Analysis Of Potential And Challenges Of Ethnoscience-Based Chemistry Learning In Madrasah Aliyah - Sri Wahyuni; Mega Novita; Muhammad Syaipul Hayat; Fenny Roshayanti (Didaktika: Jurnal Kependidikan, 2025)
This study aims to analyze the potential and challenges of ethnoscience-based chemistry learning in Madrasah Aliyah. The approach used is a quantitative survey type with participants being Madrasah Aliyah chemistry teachers in Surakarta Residency who were taken randomly. The method used is descriptive-quantitative. The data collection tool used is a questionnaire containing statements related to chemistry learning and the ethnoscience approach. Based on the data analysis carried out, both survey results and interviews, that although there is high enthusiasm from chemistry teachers, namely 92.3%, to implement ethnoscience-based learning, their knowledge of ethnoscience is still limited. As many as 50% of teachers admitted to having difficulty integrating ethnoscience with chemistry material, and 57.7% of teachers had never implemented it. The main obstacles in the implementation of ethnoscience include lack of teacher understanding and limited supporting infrastructure. Nevertheless, the ethnoscience approach offers great potential to improve scientific literacy, understanding of local culture, and student learning outcomes. Policy and infrastructure support in madrasahs, including Madrasah Aliyah Negeri Wonogiri, is ready to facilitate further development of ethnoscience-based learning. With increased training and resources, ethnoscience can be effectively integrated to enhance student engagement and understanding in chemistry learning